1997
DOI: 10.1046/j.1471-4159.1997.69041548.x
|View full text |Cite
|
Sign up to set email alerts
|

Tau Released from Paired Helical Filaments with Formic Acid or Guanidine Is Susceptible to Calpain‐Mediated Proteolysis

Abstract: Paired helical filaments (PHFs), a characteristic neuropathologic finding in Alzheimer's disease brain, are abnormal fibrillary forms of hyperphosphorylated tau (PHF-tau), which have been shown to be highly resistant to calpain digestion. Either excessive phosphorylation or fibrillary arrangement of tau proteins in PHFs may play a role in proteolytic resistance by limiting access to calpain recognition/digestion sites. To determine the contribution of the fibrillary conformation, isolated PHFs were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The amount of microtubules formed in the presence of phosphorylated P301L, V337M, and R406W is 1.7-, 1.5-, and 2. Previous studies have shown that ϳ60-, 64-, and 68-kDa tau bands of AD brain are also immunoreactive to PHF-1 antibody specific for Ser 396/404 -phosphorylated tau (51). This observation suggests that Ser 396/404 phosphorylation may also promote the formation of ϳ60-, 64-, and 68-kDa tau bands in the brain.…”
Section: Discussionmentioning
confidence: 69%
“…The amount of microtubules formed in the presence of phosphorylated P301L, V337M, and R406W is 1.7-, 1.5-, and 2. Previous studies have shown that ϳ60-, 64-, and 68-kDa tau bands of AD brain are also immunoreactive to PHF-1 antibody specific for Ser 396/404 -phosphorylated tau (51). This observation suggests that Ser 396/404 phosphorylation may also promote the formation of ϳ60-, 64-, and 68-kDa tau bands in the brain.…”
Section: Discussionmentioning
confidence: 69%
“…Results of previous studies have suggested that because of its fibrillary conformation aggregated tau is less susceptible to protease cleavage (36,37). However, no information is available regarding the generation of specific cleavage products when aggregated tau is exposed to calpain.…”
Section: The Aggregation Of Full-length Tau Into Filaments As Well Asmentioning
confidence: 99%
“…Several studies showed that tau can be degraded by calpains and phosphorylation can retard this process [35][36][37]. On the basis of the P2-P1 rule, nine potential calpain cleavage sites have been suggested for tau [38].…”
Section: Calpainsmentioning
confidence: 99%